Atorvastatin in combination with inhaled beclometasone modulates inflammatory sputum mediators in smokers with asthma. (April 2015) - Thomson, Neil C.; Charron, Catherine E.; Chaudhuri, Rekha; Spears, Mark; Ito, Kazuhiro; McSharry, Charles
Abstract: Background: Statins have pleiotropic immunomodulatory effects that may be beneficial in the treatment of asthma. We previously reported that treatment with atorvastatin improved asthma symptoms in smokers with asthma in the absence of a change in the concentration of a selection of sputum inflammatory mediators. Objective: To determine the effects of atorvastatin alone and in combination with inhaled corticosteroid on a range of sputum cytokines, chemokines and growth factors implicated in the pathogenesis of asthma, and their association with asthma control questionnaire (ACQ) and/or asthma quality of life questionnaire (AQLQ) scores. Methods: Sputum samples were analysed from a sub-group of 39 smokers with mild to moderate asthma recruited to a randomised controlled trial comparing atorvastatin (40 mg/day) versus placebo for four weeks, followed by inhaled beclometasone (400 μg/day) for a further four weeks. Induced sputum supernatant fluid was analysed (Luminex or biochemical analyses) for concentrations of 35 mediators. Results: Sputum mediator concentrations were not reduced by inhaled beclometasone alone. Atorvastatin significantly reduced sputum concentrations of CCL7, IL-12p70, sCD40L, FGF-2, CCL4, TGF-α and MMP-8 compared with placebo and, when combined with inhaled beclometasone, reduced sputum concentrations of MMP-8, IL-1β, IL-10, MMP-9, sCD40L, FGF-2, IL-7, G-CSF and CCL7 compared to ICS alone. Improvements in ACQ and/or AQLQ scores with atorvastatin and ICS were associated with decreases in G-CSF, IL-7, CCL2 and CXCL8. Conclusion: Short-term treatment with atorvastatin alone or in combination with inhaled beclometasone reduces several sputum cytokines, chemokines and growth factors concentrations unresponsive to inhaled corticosteroids alone, in smokers with asthma.